Presenilin-mediated transmembrane cleavage is required for Notch signal transduction in Drosophila. - Struhl, G.; Greenwald, I. (Proceedings of the National Academy of Sciences of the United States of America, 2001)
The cleavage model for signal transduction by receptors of the LIN-12/Notch family posits that ligand binding leads to cleavage within the transmembrane domain, so that the intracellular domain is released to translocate to the nucleus and activate target gene expression. The familial Alzheimer's disease-associated protein Presenilin is required for LIN-12/Notch signaling, and several lines of evidence suggest that Presenilin mediates the transmembrane cleavage event that releases the LIN-12/Notch intracellular domain. However, doubt was cast on this possibility by a report that Presenilin is not required for the transducing activity of N(ECN), a constitutively active transmembrane form of Notch, in Drosophila. Here, we have reassessed this finding and show instead that Presenilin is required for activity of N(ECN) for all cell fate decisions examined. Our results indicate that transmembrane cleavage and signal transduction are strictly correlated, supporting the cleavage model for signal transduction by LIN-12/Notch and a role for Presenilin in mediating the ligand-induced transmembrane cleavage.